Short Imagery Rescripting Intervention to Treat Emotionally Dysregulated Behavior in Borderline Personality Disorder: An Exploratory Study - Schaitz, Caroline; Kroener, Julia; Maier, Anna; Connemann, Bernhard J.; Sosic-Vasic, Zrinka (Frontiers in Psychiatry, 2020)
Background: Current research on borderline personality disorder report an association between emotionally dysregulated behaviors and intrusive mental imagery depicting similar scenes. Imagery rescripting techniques have proven effective in reducing intrusive mental imagery in numerous contexts. We developed a two session-short intervention in which intrusive mental images are identified, analyzed, and modified for daily rehearsal at home. This study aimed to reduce the negative emotions and cognitions associated with self-injurious behaviors by replacing unhealthy imagery with more adaptive content. Methods: Seven females diagnosed with borderline personality disorder who reported intrusive mental imagery of dysregulated behaviors were recruited for participation. Each participant engaged in two individualized treatment sessions and daily homework requiring the rehearsal of modified imagery. Emotion regulation strategies, borderline symptom severity, and depressiveness were assessed before and after treatment. Results: Acceptance was positive, as no patient dropped out from treatment. Symptom exacerbation was not observed. Borderline symptom reduction was noted and indicia of emotional dysregulation and negative affect declined. Limitations: The generalizability of results is limited by small sample size and the absence of a control group. Conclusions: This new two-session short intervention was shown to decrease the emotionally dysregulated behaviors that accompany negative feelings in females with borderline personality disorder.